Visit-to-Visit Fasting Glucose Variability in Young Adulthood and Cardiac Structure and Function at Midlife: The CARDIA Study - Xiong, Zhenyu; Xie, Peihan; Li, Jiaying; Chen, Zhi-chong; Lin, Yifen; Liu, Menghui; Zhang, Shaozhao; Zhong, Xiangbin; Zhou, Huimin; Zhuang, Xiaodong; Liao, Xinxue (Frontiers in Cardiovascular Medicine, 2021)
Glycemic variability was found associated with left ventricular structure and function in type 2 diabetes. But it is still unclear that whether the greater visit-to-visit fasting glucose (FG) variability in young adulthood among community population is associated with cardiac function alteration and cardiac remodeling at midlife. The community-based prospective cohort study of Coronary Artery Risk in Young Adult (CARDIA) recruited young participants at the baseline age of 18 to 30 during 1985 to 1986 (Year 0). FG was measured at Year 0, 2, 10, 15, 20 and 25. And echocardiographic evaluation of cardiac structure and function was conducted at year 25. A total of 2600 young adults mean (SD) aged at 24.9 (3.6) of which 57.3% were women and 46.7% were black had been included in the study. After multivariable adjusted, higher SDFG is associated with lower e’ (β [SE], -0.214[0.080], P<0.01) and higher E/e’ (β [SE], 0.307[0.094], P<0.01), and higher CVFG is also associated with lower e’ (β [SE], -0.141[0.066], P<0.05) and higher E/e’ (β [SE], 0.204[0.078], P<0.01). Higher ARVFG is associated with higher E/e’ (β [SE], 0.178[0.085], P<0.05) and higher LVMI (β [SE], 1.240[0.618], P<0.05). Higher fasting glucose variability in young adulthood is associated with subclinical change of LV diastolic function at midlife.